(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2013)
Every year worldwide about 42 million women with unintended pregnancies choose abortion, and nearly half of these procedures, 19 million, are unsafe. Some 70,000 women die of unsafe abortion annually, making it one of the leading causes of maternal mortality (13%). Of the women who survive unsafe abortion, 5 million will suffer longterm health complications. Unsafe abortion is thus a pressing issue. Both of the primary methods for preventing unsafe abortionless restrictive abortion laws and greater contraceptive useface social, religious, and political obstacles, particularly in developing countries, where most unsafe abortions (97%) occur. Even where these obstacles are overcome, women and health care providers need to be educated about contraception and the availability of legal and safe abortion, and women need better access to safe abortion and post abortion services. Otherwise, desperate women, facing the financial burdens and social stigma of unintended pregnancy and believing they have no other option, will continue to risk their lives by undergoing unsafe abortions. According to the World Health Organization (WHO), every 8 minutes a woman in a developing nation die of complications arising from an unsafe abortion. The fifth United Nations Millennium Development Goal recommends a 75% reduction in maternal mortality by 2015. WHO deems unsafe abortion one of the easiest preventable causes of maternal mortality and a staggering public health issue. We report a case of a 21 years female who presented with uterine perforation with small intestinal prolapse through uterine perforation that required repair of uterine perforation with resection anstomosis of small gut after a unsafe abortion of a 16 weeks pregnancy. JCMCTA 2012 ; 23 (2): 50-52